Antimicrobial resistance in coagulase-positive staphylococci (CoPS) isolated from dogs with external otitis - Palomino-Farfán, Joel André (2020)
The coagulase-positive staphylococci (CoPS) group includes the species S. aureus, S. pseudintermedius, S. intermedius and S. schleiferi subsp. coagulans. The purpose of this study was to evaluate the antimicrobial resistance of CoPS isolated from dogs with external otitis, using the most commonly antibiotics prescribed in the daily clinic to treat this disease. Samples of ear secretions (n=148) were obtained from 104 dogs with external otitis treated in a veterinary clinic in Lima, Peru in a period of six months. Among them, 113 isolates were identified as Staphylococcus sp, of which 105 were CoPS. The isolates showed the greatest resistance to resistance to ciprofloxacin (27.4%) and the greatest sensitivity to nitrofurantoin (82.1%).